2010
DOI: 10.1007/s10815-010-9392-9
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive outcome of female patients with myotonic dystrophy type 1 (DM1) undergoing PGD is not affected by the size of the expanded CTG repeat tract

Abstract: Purpose This study aims to analyze the relationship between trinucleotide repeat length and reproductive outcome in a large cohort of DM1 patients undergoing ICSI and PGD. Methods Prospective cohort study. The effect of trinucleotide repeat length on reproductive outcome per patient was analyzed using bivariate analysis (T-test) and multivariate analysis using Kaplan-Meier and Cox regression analysis. Results Between 1995 and 2005, 205 cycles of ICSI and PGD were carried out for DM1 in 78 couples. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
12
1
2
Order By: Relevance
“…However, the relationship between the number of CTG repeats and fertility is not clear. The length of the trinucleotide repeat does not correlate with ovarian reserve (Dechanet et al, 2010) or with the probability of live birth (Verpoest et al, 2010). It is possible that the expanded DMPK mRNA also accumulates in ovarian granulosa cells and may contribute to impaired ovarian function, in addition to a probable decreased fertility due to the multisystemic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the number of CTG repeats and fertility is not clear. The length of the trinucleotide repeat does not correlate with ovarian reserve (Dechanet et al, 2010) or with the probability of live birth (Verpoest et al, 2010). It is possible that the expanded DMPK mRNA also accumulates in ovarian granulosa cells and may contribute to impaired ovarian function, in addition to a probable decreased fertility due to the multisystemic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that women with DM have worse response to ovarian stimulation and lower pregnancy rates compared with carriers of X-linked disorders (Feyereisen et al, 2006) or women undergoing IVF/intracytoplasmic sperm injection (ICSI) due to male infertility (Sahu et al, 2008). Other investigators have found no association between the disease and the number of CTG repeats with IVF or PGD outcome (Dechanet et al, 2010;Verpoest et al, 2008Verpoest et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The current clinical classi cation of DM1 is based on age at onset and CTG length [7,12,13,34,35]. On the other hand, several reports have shown no evidence of an effect of CTG repeat length on clinical severity [8,11,36]. Since the severity of CDM depends on the status of respiratory complications [6], prematurity is supposed to worsen respiratory status.…”
Section: Discussionmentioning
confidence: 99%
“…Bei der Auswertung der PKD-Daten unseres Zentrums beobachteten wir wie zuvor andere Gruppen [13] selektiv eine geringere Schwangerschaftsrate von nur 16,1 % pro Transfer für die Subgruppe der weiblichen Überträgerinnen für DMPK und die FMR1-Prämutation, während wir für die non-Rx mit 25,3 % Behandlungsergebnisse nahe des Durchschnitts im Deutschen DIR-Register erreichten [3]. Aufgrund unserer besseren vorläufigen Behandlungsergebnisse mit der TED kann u. E. für diese weiblichen Überträgerinnen der myotonen Dystrophie Typ 1 oder einer FMR1-Prämutation eine PKD nicht mehr empfohlen werden, sie sollten bei dem Wunsch nach einer PID auf die TED verwiesen werden.…”
Section: Diskussionunclassified